Behavior Therapy in Curing Depression for Adolescents with Sickle Cell Disease - Tolulope Taiwo; Olayinka Atilola; Cornelius Ani; Bola A. Ola (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
Depression has been identified as one of the commonest mental-health problems in SCD, with prevalence rates as high as 27% - 46% reported [1]. While psychological therapies have been found to be beneficial in mild to moderate depression, their use as non-pharmacological methods amongst adolescents in sub-Saharan Africa, particularly Nigeria, is still at its infancy. This chapter determines the effect of behavioural activation therapy on depression in adolescents living with Sickle Cell Disease attending out-patient clinic at the Lagos State University Teaching Hospital, Lagos, Nigeria. The study was conducted in Lagos State University Teaching Hospital, Lagos, Nigeria, between November 2017 to February 2018 (4 months) among adolescents living with SCD and depression attending out-patient clinic. The participants were a sample of consenting adolescents (12 - 17 years) with SCD who had mild to moderate depression. We excluded those with severe depression on anti-depressant medications. The participants were divided into two groups, the treatment group and wait list (control) group. A randomized control trial (RCT) was conducted among participants assigned to treatment (30) versus control (30) group. A manualized behavioral therapy programme developed was delivered to the treatment group. The data was analysed using the Statistical Package for Social Sciences (SPSS) version 23. Pair T-test was used to compare the two groups across continuous variables, pre- and post-intervention. Analysis of Covariance (ANCOVA) was used to deter- mine treatment effects controlling for baseline scores. After the inter- vention, the mean depression score reduced from 22.13 ± 3.08 to 13.02 ± 4.56 while Paediatric quality of life score increase from 62.57 ± 17.85 to 67.90 ± 7.99 in the treatment group (BDI, p < 0.001; PedsQL, p = 0.045). However, the pre- and post-intervention mean depression scores in the control group showed insignificant reduction from 22.23 ± 3.24 to 21.60 ± 2.75 and mean PedsQL from pre-intervention scores of 59.67 ± 12.60 to 56.73 ± 8.94 post intervention (BDI, p = 0.388; PedsQL, p = 0.242). From multivariate analysis (ANCOVA), only the Quality of Life scores ceased to show any significant effect of the intervention. In conclusion, the effect of behavioral activation therapy (BAT) in adolescents with SCD and mild to moderate depression using a randomized controlled trial has been developed. The results reflected that BAT resulted in significant improvements in self-reported rating of depressive symptoms (effect size 2.1) and depression literacy suggesting efficacy of BAT in alleviating depressive symptoms in this cohort, however the QoL scores initially appeared to have had a positive change but ceased to be so after controlling for possible confounders.